Relationship between the level of physical activity and anxiety, stress and depression in Chilean adults in the context of the covid-19 virus pandemic (Revista Chilena de Rehabilitación y Actividad Física, 2022)
Introduction: With the arrival of the Covid-19 virus, the Chilean population was faced with a series of social restrictions to prevent the spread of the virus. These restrictions limited the development of physical activity and led to changes in people’s mental health, such as stress, anxiety and depression. Objective: The purpose of this study was to determine the relationship between physical activity and levels of stress, anxiety and depression. Methodology: A cross-sectional study of correlational type was carried out, with a non-experimental and cross-sectional design, where an online survey was applied, which allowed determining the levels of physical activity (low, moderate and high level) and establishing the levels of stress, anxiety and depression of the study population, for this two measurement instruments were applied, the International Physical Activity Questionnaire (IPAQ) and the DASS-21 survey to measure anxiety, depression and stress. As for the sample, it was composed of 71 people. Results: The results show a correlation between the levels of physical activity and stress with a p=0.002 with a moderate variance r = -0.366. In turn, there is a correlation between levels of physical activity and depression with a p=0.002 with a moderate variance of r = -0.356; demonstrating that the higher the level of physical activity, the lower the levels of stress and depression in the subjects surveyed. There is no relationship between levels of physical activity and anxiety. Conclusion: We can conclude that there is a relationship between levels of physical activity and levels of stress and depression, but not with anxiety levels.
Keywords: Physical activity; depression; anxiety; stress